(3OQ GdMHH aj JGQjN CYjGf MdHs - (3eMeO Hf EHQGgje Hf jhSa GdMdHj GdbGOQj GdJGPaj, QVj GdOjf GHf GdMfHdj, jJUd fSHg HGHf GdTMfI,J (B971 (3g` s ((3YHO GdQMje CafOi GScfOQ RGOg s)
(3ChdgG (B:s
(3GdMeO ddg eHjO GdChGFd hGdChGNQ s
(3BNQgG (B:s
(3gPG BNQ eG hLO ef gPG GdJGQjN s
(3GfXQ GdbSe GdChd Qbe (B239 (3hGdbSe GdKGfi Qbe (B649s
(3QJHg Ydi MQha GdeYLes
(3cJHJ HQSe bGVi GdbVGg YHO GdQMje CafOi GScfOQ RGOgs
(3fSNI NGeSI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs